Analisis Literatur Tentang Prinsip Bernoulli Dalam Desain Aliran Fluida - Harefa, Daman; Giawa, Andel (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
The design of  Bernoulli's law experiment tool was designed for finding out the relationship between the pressure and the speed of the fluid’s flow according Bernoulli's law statements and know the standard deviation of Bernoulli's law tool. This tool was designed based on the basic and principle of ideal fluid flowing through a pipe from the fisrt bottle  into the second bottle which  hung on a statif modification. Design of this tool were  simple so it was easy to do experiment. The experiment results were do twice where the first experiment applied on the condition both of firs bottleand second bottle was same in height and for the second experiment  the first bottle and the second bottle was different in height. The first experiment showed the water would stop for  flowing when the high of  water in the first bottle and second bottle were  the same unless for the second experiment the water was stops flowing when the difference height of water in the bottle as same as the difference between the first bottle’s height with the second bottle’s height. The result of experiment proved the tool that has designed showed  the level of error for the first experiment was 6.97% with the average speed of the fluid’s flow (43 ± 2) 10-3 cm3/s and the error level for second experiment was 9.99% with the average speed of the fluid’s flow (43 ± 3) 10-3 cm3/s.